2009
DOI: 10.1667/rr1648.1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Acute Myeloid Leukemia and Hepatocellular Carcinoma in Mice Irradiated with 1 GeV/nucleon56Fe Ions

Abstract: Estimates of cancer risks posed to space-flight crews by exposure to high atomic number, high-energy (HZE) ions are subject to considerable uncertainty because epidemiological data do not exist for human populations exposed to similar radiation qualities. We assessed the leukemogenic efficacy of one such HZE species, 1 GeV (56)Fe ions, a component of space radiation, in a mouse model for radiation-induced acute myeloid leukemia. CBA/CaJ mice were irradiated with 1 GeV/nucleon (56)Fe ions or (137)Cs gamma rays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 30 publications
11
90
0
Order By: Relevance
“…Proton is ~ 50%, helium is ~25% and HZE particles with high-LET is ~25% of a given GCR simulation dose. Combining such information with previously published data that showed high-versus low-LET radiation induced a higher incidence of tumorigenesis in different mouse models (Fry et al, 1983;Trani et al, 2014;Ullrich et al, 1987;Wang et al, 2015;Weil et al, 2009), and the real risk of space radiation-induced tumorigenesis might be lower than previously estimated since high-LET radiation takes ~1/4 of total space radiation. Such a prediction needs further experiments to verify.…”
Section: Accepted Manuscriptsupporting
confidence: 61%
See 1 more Smart Citation
“…Proton is ~ 50%, helium is ~25% and HZE particles with high-LET is ~25% of a given GCR simulation dose. Combining such information with previously published data that showed high-versus low-LET radiation induced a higher incidence of tumorigenesis in different mouse models (Fry et al, 1983;Trani et al, 2014;Ullrich et al, 1987;Wang et al, 2015;Weil et al, 2009), and the real risk of space radiation-induced tumorigenesis might be lower than previously estimated since high-LET radiation takes ~1/4 of total space radiation. Such a prediction needs further experiments to verify.…”
Section: Accepted Manuscriptsupporting
confidence: 61%
“…However, due to a lack of epidemiologic data for high-LET radiation exposure, it is highly uncertain how high the risk of lung carcinogenesis is for astronauts following exposure to space radiation (Durante and Cucinotta, 2008), and evaluating the space radiation risk depends primarily on animal experiments. Previously, different groups using different mouse models demonstrated that high-LET radiation versus low-LET radiation has a higher risk of generating tumorigenesis in the Harderian gland (Fry et al, 1983), lung (Ullrich et al, 1987), mammary (Ullrich et al, 1987), liver (Weil et al, 2009) and colon (Trani et al, 2014). These data provide valuable information for estimating the risk of space radiation with high-LET HZE particle-induced tumorigenesis.…”
Section: Introductionmentioning
confidence: 95%
“…Several reports (Fry et al, 1985;Alpen et al, 1993;Dicello et al, 2004;Weil et al, 2009Weil et al, , 2014Grahn et al, 1992;Imaoka et al, 2007;Trani et al, 2010;Datta et al, 2013;Illa-Bochaca et al, 2014;Wang et al, 2015) have suggested that HZE particles and neutrons could produce more lethal tumors compared to tumors produced by low LET radiation or background tumors, which is a qualitative difference not accounted for in current risk estimates. Table 3 summarizes these findings from animal studies with HZE particle beams.…”
Section: Tumor Modelmentioning
confidence: 96%
“…For instance, recent work at the Brookhaven National Laboratory accelerator has shown that the RBE of 1 GeV n 21 Fe-ions for cancer induction in mice is about 1 for leukaemia and about 20 for hepatocellular carcinoma. 119 How can the RBE be so different? The reason is most likely because of the different nature of liquid and solid cancers.…”
Section: Late Effectsmentioning
confidence: 99%